Comparing the Sensitivity and Specificity of Lung CT-scan with RT-PCR for Diagnosis of COVID-19 - Asghari, Akram; Adeli, Seyed-Hasan; Parham, Mahmoud; Bagherzade, Mohammad; Ahmadpour, Sajjad; Shajari, Rasoul; Tabarrai, Reihane; Shakeri, Masoumeh; Habibi, Mohammad A.; Jabbari, Amir; Jafari, Saeede; Razavinia, Fatemesadat; et al. (Current Medical Imaging, 2023)
Background: The lung is one of the major organs affected by the SARS-CoV-2 virus. Lung CT scan and RT-PCR are the most valuable diagnostic methods in the early diagnosis and management of COVID-19. Due to the possible inconsistency of the false-negative results for the RT-PCR test, in our study, we aimed to evaluate the sensitivity and specificity of lung CT-scan as an accurate diagnostic method of COVID-19. Methods: In this cross-sectional study, patients suspected of COVID-19 and referred to Shahid Beheshti Hospital in Qom city from February 26 to April 13, 2020, were enrolled. For a definitive diagnosis of COVID-19, chest CT scan and RT-PCR testing was performed for 644 patients, and both sensitivity and specificity of lung CT scan were evaluated. Results: According to the findings, and comparing to the RT-PCR test as the gold standard, sensitivity, specificity as well as, positive predictive and negative predictive values of lung CT-scan were found as follow; 94.47% (95% CI: 90.73 - 97.02%), 24.71% (95% CI: 20.70 - 29.07%), 40.73% (95% CI: 36.58 - 44.99%), 89.08% (95% CI: 82.4 - 94.05%), respectively. Conclusion: According to the findings, the lung CT scan has a better diagnostic value than RTPCR in symptomatic patients who were referred to the hospital for COVID-19 diagnosis. Performing lung CT-scan in patients with negative RT-PCR tests should be assessed.
Keywords: COVID-19